solution of transcedental equation
1 Ansicht (letzte 30 Tage)
Ältere Kommentare anzeigen
shiv gaur
am 14 Okt. 2021
Kommentiert: Matt J
am 14 Okt. 2021
function beta1 = trial0(beta, eps1, eps2, epsm,k0,h)
S1 = sqrt(power(beta,2)-(eps1*power(k0,2)));
S2 = sqrt(power(beta,2)-(epsm*power(k0,2)));
S3 = sqrt(power(beta,2)-(eps2*power(k0,2)));
beta1 = tanh(S2*h)*((eps1*eps2*power(S2,2))+(power(epsm,2)*S1*S3)) + (S2*((eps1*S3)+(eps2*S1))*epsm);
end
eps1 = 1.5471;
eps2 = 1.5431;
eps1m = -9.894 ;
epsm2 = 1.0458;
epsm = eps1m + i*eps2m;
lambda = 633;
k0 = (2*pi)/lambda;
h = 50;
find the value of beta
1 Kommentar
Catalytic
am 14 Okt. 2021
You have not accepted any answers previously provided to you. That is a bit of a disincentive for people to help you.
Akzeptierte Antwort
Matt J
am 14 Okt. 2021
Bearbeitet: Matt J
am 14 Okt. 2021
eps1 = 1.5471;
eps2 = 1.5431;
eps1m = -9.894 ;
eps2m = 1.0458;
epsm = eps1m + i*eps2m;
lambda = 633;
k0 = (2*pi)/lambda;
h = 50;
[b,fval]=fminsearch(@(b) abs(trial0(complex(b(1),b(2)), eps1, eps2, epsm,k0,h)) ,[1,1]);
beta=complex(b(1),b(2)), fval
function beta1 = trial0(beta, eps1, eps2, epsm,k0,h)
S1 = sqrt(power(beta,2)-(eps1*power(k0,2)));
S2 = sqrt(power(beta,2)-(epsm*power(k0,2)));
S3 = sqrt(power(beta,2)-(eps2*power(k0,2)));
beta1 = tanh(S2*h)*((eps1*eps2*power(S2,2))+(power(epsm,2)*S1*S3)) + (S2*((eps1*S3)+(eps2*S1))*epsm);
end
7 Kommentare
Matt J
am 14 Okt. 2021
Well, if we've answered your first question, please Accept-click it and post the related question in its own thread.
Weitere Antworten (0)
Siehe auch
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!